Combined glycated hemoglobin index and red cell distribution width predict in-hospital mortality in critically ill sepsis patients based on MIMIC-IV analysis - Huan Xu; Jiaojian Lv; Feifei Lin; Luxiang Liu (Scientific Reports)
Abstract Red cell distribution width (RDW) and glycated hemoglobin index (HGI) is considered an important tool for assessing the prognosis of sepsis patients, closely related to the risk of mortality associated with sepsis. This study investigates the association between the HGI combined with RDW and the risk of in-hospital mortality in patients with sepsis. We analyzed data from 13,726 sepsis patients who were admitted to the intensive care unit (ICU) for more than 24 h, sourced from the American Medical Information Mart for Intensive Care (MIMIC-IV) database. Kaplan-Meier survival curves and multivariable Cox regression analyses were employed to assess the impact of various variables on patient outcomes, stratified by quartiles of HGI and RDW. Additionally, restricted cubic spline (RCS) analysis was utilized to explore how changes in HGI and RDW might influence the studied outcomes. The results indicated that the highest quartile (Q4) of the combined metrics significantly increased in-hospital mortality compared to the lowest quartile (Q1) (p < 0.0001). Multivariable Cox regression analysis revealed that patients in Q4 faced the highest risk of in-hospital mortality (hazard ratio: 1.22, 95% confidence interval: [1.10–1.36], p < 0.001). RCS analysis demonstrated a nonlinear relationship between HGI-RDW and the risk of adverse outcomes. Further analysis identified significantly elevated risks in patients over 65 years old, those who were widowed, those receiving macrolide antibiotics, and those with congestive heart failure or severe liver disease. In conclusion, elevated levels of the combined HGI and RDW metrics are independent risk factors for adverse outcomes in critically ill patients with sepsis, associated with increased mortality.